A systematic decision-making approach for planning and assessment of hybrid renewable energy-based microgrid with techno-economic optimization: A case study on an urban community in Egypt. (March 2020) - Elkadeem, M.R.; Wang, Shaorong; Azmy, Ahmed M.; Atiya, Eman G.; Ullah, Zia; Sharshir, Swellam W.
Graphical abstract: Highlights: A systematic approach for efficient planning and design of HRE-MG system is proposed. PV/WT/FC/DiG/BAT/CONV HRE-MG is optimized to meet electrical and thermal demands of a small urban area in Egypt. Effect of LPSP and uncertainty parameters on the system profitability is examined. PV/WT/FC/BAT/CONV configuration is a cost-effective and reliable design. Load growth has a high influence on investment decision rather RE resources. Abstract: This paper proposes a systematic and integrative decision-making approach for efficient planning and assessment of hybrid renewable energy-based microgrid (HRE-MG) systems. The approach is combined with an extensive techno-economic optimization analysis. The proposed methodology is validated with an actual case study on an urban city in Egypt, with the developed HRE-MG comprising solar, wind, diesel, and fuel cell energies. Different hybridization scenarios are modeled, evaluated and compared to obtain the most practicable solution with minimum cost and emission impact. The obtained results reveal that solar, wind, fuel cell show optimal configuration plan that yields a minimum net present and energy costs. Also, it achieves a significant reduction in carbon gases and increases system renewable fraction compared to other scenarios. Further, the reliability of the proposed hybrid energy system is examined under loss of power supply probability concept. A sensitivity analysis is then conducted to verify the model accuracy and examine the cost performance of the designed system concerning uncertain parameters.